PENERAPAN METODE FUN TEACHING PADA PEMBELAJARAN TEMATIK KELAS III DI SD ASSUNNAH ASSALAFIYYAH SURALAGA KECAMATAN SURALAGA - Munawir Gazali; Made Ayu Pransisca; Lalu Juwita Efendi (Jurnal Ilmiah Global Education, 2023)
In this research discusses the aplication of the Fun Teaching method in thematic learning in grade III SD Assunnah  Assalafiyyah Suralaga. The purpose of this research is to find out the aplication of the Fun Teaching method in thematic learning at SD Assunnah  Assalafiyyah Suralaga and to find out the factors that support and hinder learning in progress. This research is a qualitative descriptive study with data sources comng from observations, interviews, and documentation. Techniques to guarantee the validity of the data using extend observations increase persistence, and triangulation. This study found that applying the fun teaching method was very successful, seen from their seriousness in doing the task, their activeness in asking questions and not being afraid when the teacher taught, so that passive students were actively involved during the learning process. By applying this fun teaching method, students are challenged when given assignments by teacher, their active role is seen from when doing assignments both individually and in groups. Based on the discussion, it was concluded that the application of the Fun Teaching method in thematic learning at SD Assunnah  Assalafiyyah Suralaga which was carried out by the teacher while in grade III wen well. Supporting factors in learning in grade III SD Assunnah  Assalafiyyah Suralaga are adequate or complete facilities and infrastructure, and increased teacher-student interaction. As for the inhibiting factors in thematic learning for grade III SD Assunnah  Assalafiyyah Suralaga, namely in terms of teachers and students regarding theatic learning in class, constraints of limited time, and incomplete facilities and infrastructure.